THE IMPACT OF GEOPOLITICAL PRESSURE PROXIED BY AVTUR PRICES ON THE FINANCIAL PERFORMANCE OF AIRLINES LISTED ON THE INDONESIAN STOCK EXCHANGE: THE MEDIATION ROLE OF OPERATIONAL COSTS - Qory Meidina Izria; Pramudi Harsono; Surti Zahra (Yayasan Education and Social Center, 2026)
This study analyzes the effect of geopolitical pressure in the energy market, proxied by aviation fuel prices, on the financial performance of airlines listed on the Indonesia Stock Exchange, with operating costs as a mediating variable. Financial performance is measured using Return on Equity (ROE). This research applies a quantitative associative-causal approach using quarterly panel data from 2022 to 2025 on two airline issuers, namely PT AirAsia Indonesia Tbk (CMPP) and PT Garuda Indonesia (Persero) Tbk (GIAA), resulting in 32 observations. Financial data were obtained from public financial reports, while aviation fuel price data were collected from official aviation fuel price sources. Aviation fuel prices and operating costs were transformed into natural logarithms to ensure proportional data scaling. The data were analyzed using linear regression, path analysis, and the Sobel test with SPSS 25. The results show that aviation fuel prices do not have a significant direct effect on ROE (β = -0.054; t = -1.424; p = 0.165). Aviation fuel prices have a positive and significant effect on operating costs (β = 0.624; t = 3.386; p = 0.002), while operating costs have a negative and significant effect on ROE (β = -0.881; t = -2.452; p = 0.020). Mediation testing indicates that operating costs fully mediate the effect of aviation fuel prices on ROE (indirect effect = -0.550; Sobel t = -4.92). These findings indicate that the impact of geopolitical pressure on airline profitability primarily occurs through increased operating costs. The study implies the importance of cost efficiency, fuel consumption management, and mitigation strategies against aviation fuel price volatility.